(untitled) (Confluenţe Bibliologice, 2013)
Various studies, monographs, encyclopedias and dictionaries, where there are data about Alexei Mateevici, does not oﬀer authentic information about the death of the poet, whose poem "Limba Noastra" became the National Anthem of the Republic of Moldova. Some sources claim that he died during military campaigns of World War I on August 13th 1917, others that the poet catched a disease, which brings premature end to Mateevici on 26 August 1917, others argue that he died at Chisinau by abdominal typhus, but not exanthemum. Conﬂicting informations were the basis of this study of the medical expert in Moldova.